The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/s22103752
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered and Autonomous Vibrational Wake-Up System Based on Triboelectric Nanogenerators and MEMS Switch

Abstract: With the extensive application of wireless sensing nodes, the demand for sustainable energy in unattended environments is increasing. Here, we report a self-powered and autonomous vibrational wake-up system (SAVWS) based on triboelectric nanogenerators and micro-electromechanical system (MEMS) switches. The energy triboelectric nanogenerator (E-TENG) harvests vibration energy to power the wireless transmitter through a MEMS switch. The signal triboelectric nanogenerator (S-TENG) controls the state of the MEMS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In other works, they also proposed the up-and-down distributed dual TENGs system [74,77] installed on mechanical equipment and used the energy from vibration of machines to monitor their working state. Researchers have carried out a large number of experimental research and theoretical analysis on the four springs-assisted TENG.…”
Section: Spring-based Vehmentioning
confidence: 99%
“…In other works, they also proposed the up-and-down distributed dual TENGs system [74,77] installed on mechanical equipment and used the energy from vibration of machines to monitor their working state. Researchers have carried out a large number of experimental research and theoretical analysis on the four springs-assisted TENG.…”
Section: Spring-based Vehmentioning
confidence: 99%
“…The electric current of the TENG is used to sense vibration acceleration changes with a maximum vibration sensing resolution of 23.4 nA•m −1 •s 2 . In addition, as shown in Figure 16m, Lin et al [609] developed a self-powered autonomous vibration wake-up system. The system's TENG acts as an accelerometer with a sensitivity of 14.6 V/(m s −2 ).…”
Section: Self-powered Microelectronics In Smart Industrymentioning
confidence: 99%
“…[25][26][27] For example, the TENG has been applied to self-powered position monitoring. [28][29][30] Zi et al [31] reported a smart buoy hybrid generator for harvesting water wave energy to drive a selfpowered wireless positioning system that can send a signal via GPS half an hour after harvesting the energy. Kim et al report a boat-shaped hybrid nanogenerator for energy harvesting, navigation, and tracking of fishing nets to determine buoy position, which can charge a commercial battery to 3 V in 9000 s to drive GPS.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25–27 ] For example, the TENG has been applied to self‐powered position monitoring. [ 28–30 ] Zi et al. [ 31 ] reported a smart buoy hybrid generator for harvesting water wave energy to drive a self‐powered wireless positioning system that can send a signal via GPS half an hour after harvesting the energy.…”
Section: Introductionmentioning
confidence: 99%